A review of difference between Inclusive Education and Integrated Education - Kumar, Rajesh (Innovative Research Thoughts, 2017)
Every kid is the nation's priority. They are the country's future citizens. Individual people must contribute to the development of a country. For this reason, the country is concerned about all children's health, happiness, accomplishment, contribution, safety, and success. One of the most recent initiatives toward accomplishing this aim is the Right of Children to Free and Compulsory Education Act (RTE Act 2009). Our role as educators is critical in achieving this national goal. Our active engagement in this process is critical in empowering all students, regardless of their differences. In education, the phrases inclusion and integration are used interchangeably. The distinction between inclusion and integration is that in integration, the special needs kid is integrated into the mainstream education, while this does not happen in inclusion. Both of these techniques are essential for giving successful education to the world's different youngsters.